Non-coding RNA and hepatitis B virus-related hepatocellular carcinoma: A bibliometric analysis and systematic review - Yan, Li-rong; Liu, Ao-ran; Jiang, Li-yue; Wang, Ben-gang (Frontiers in Medicine, 2022)
Objective: A bibliometric analysis of noncoding RNA and hepatitis B virus (HBV) related hepatocellular carcinoma was performed to describe the current international situation in this field and visualize its research scope and emerging trends. Methods: The data of noncoding RNA and HBV-related hepatocellular carcinoma retrieved and extracted from the Web of Science Core Collection (WoSCC) database from January 1, 2003, to June 13, 2022, were analyzed by a bibliometric method. In total, 1,036 articles published in this field were assessed for specific characteristics, including year of publication, journal, author, institution, country/region, references, and keywords. VOSviewer was used to perform co-authorship, co-occurrence, and co-citation analyses and build a visual network. Results: Overall, 1,036 reports on noncoding RNA and HBV-related hepatocellular carcinoma published from 2003 to 2022 were found in WoSCC. Over the last two decades, there has been a gradual increase the publication of reports on noncoding RNA and HBV-related hepatocellular carcinoma. Such reports have been published in 324 journals. PLOS One has the most publications (n=45), followed by World Journal of Gastroenterology (n=33), and Scientific Reports (n=32). China is the country with the most research results (748 publications, 23,184 citations), Fudan University is the most productive institution in this field (60 publications, 2,649 citations), while Zhang Xiaodong (19 publications, 1,096 citations) and Tang Hua (19 publications, 547 citations) are the most productive authors. A co-occurrence cluster analysis of the top 100 keywords was conducted and produced four clusters: (1) noncoding RNA as a molecular marker for the diagnosis and prognosis of HBV-related hepatocellular carcinoma; (2) dysregulation of the expression of noncoding RNA by hepatitis B virus X protein (HBx); (3) noncoding RNA affecting the biological behavior of HBV-related hepatocellular carcinoma; and (4) epidemiological study of the effect of noncoding RNA on the risk of HBV-related hepatocellular carcinoma. Conclusions: The number of publications and citations related to noncoding RNA and HBV-related hepatocellular carcinoma have increased in many countries and institutions, with many more authors publishing reports in this field. This study reveals the current developmental trends, global modes of cooperation, basic knowledge, research hotspots, and emerging frontiers in this field.